LEADING TRADITIONAL AND RISING POWERS AS SECURITY PROVIDERS IN THE WORLD MOST FRAGILE STATES - M. L. Gorbunova; I. D. Komarov (Сравнительная политика, 2020)
The article explores the resource capabilities and strategies the traditional and rising powers use to bring food, energy and military-political security to the world most fragile states. There is a certain complementarity in the relations between both the mentioned actors in international relations, since the negative externalities forming in and around fragile states require resources that could be provided and effectively provided by the world most powerful countries. The assumption that the key characteristic of a power (center) is a capability to translate outside military-political security allowed to the authors to categorize the USA, EU and, with certain restrictions, Japan as traditional centers of power; while Russia, China, Brazil, Turkey, and, to a lesser extent, India and Korea as rising ones. In terms of quantitative parameters, the United States, the EU, India and Russia have the resources to ensure food security, while Russia is the only major power that has a net surplus in energy foreign trade. Russia's comprehensive resource capability in the context of “broad” security supports its leadership status in its efforts to stabilize and maintain the world order. Considering the behavioral and not resource aspect, the strategies of global and middle powers in the world most fragile states, with the exception for the EU and Turkey, correspond to their resource capabilities. Both deliver mineral fuels as well as Turkey supplies crops to fragile countries having overall deﬁ cit of such commodities. This may indicate that these centers of power as well as Russia implement the “donor” strategies conceptualized in the literature for the rising powers of the modern world order.